Flourish. Banner. Frame 555 ornaments and motifs for design and illustration - Glitschka, Von (Cincinnati, Ohio How Books, 2011)
"A library of 5555 original symbols, floral motifs, border treatments, frills, banners, shields, crests, ornaments, decorative frames, placards and cartouches. Each design element has been crafted with vector precision, and you can use this artwork within the context of your own projects, whether they are personal or professional in nature"--Back cover
"All source files on the DVD are saved as both native Adobe CS2 and CS4 .ai files"--Back cover
"DVD includes editable vector files, quick reference index and usage samples."
Systems requirements for accompanying DVD-ROM: Macintosh with OSX or PC with Windows XP, 512 MB of RAM, Adobe CS2 Illustrator
1
NEW, ARTS
Keywords: Borders, Ornamental (Decorative arts); Clip art; Picture frames and framing; Printers' ornaments